1998
DOI: 10.1677/joe.0.1590501
|View full text |Cite
|
Sign up to set email alerts
|

Fetal programming of insulin-like growth factor (IGF)-I and IGF-binding protein-3: evidence for an altered response to undernutrition in late gestation following exposure to periconceptual undernutrition in the sheep

Abstract: It has been demonstrated in several animal models that undernutrition in utero has significant long lasting effects on subsequent fetal and postnatal development. To address the hypothesis that the insulin-like growth factors (IGFs) may mediate such effects, our study examined whether a period of periconceptual maternal undernutrition could have a lasting influence on the IGF axis in the fetal sheep. Ewes were either allowed to feed ad libitum or kept undernourished from day 60 prior to mating until day 30 aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 35 publications
4
40
1
1
Order By: Relevance
“…This change in plasma IGF-1 levels correlates well with the absolute fetal weights under nutrition restriction (29.9% reduction) and overfeeding (22.2% increase). Earlier studies have indicated that maternal undernutrition during periconceptual and gestational periods may lead to significant falls in fetal IGF and IGF binding protein-3 (IGFBP-3) levels in sheep (17,20). Nonetheless, our data favored a role of IGF-1 rather than IGF-1R or IGFBP3 in altered fetal heart weights in response to nutrition restriction and overfeeding.…”
Section: Discussioncontrasting
confidence: 44%
“…This change in plasma IGF-1 levels correlates well with the absolute fetal weights under nutrition restriction (29.9% reduction) and overfeeding (22.2% increase). Earlier studies have indicated that maternal undernutrition during periconceptual and gestational periods may lead to significant falls in fetal IGF and IGF binding protein-3 (IGFBP-3) levels in sheep (17,20). Nonetheless, our data favored a role of IGF-1 rather than IGF-1R or IGFBP3 in altered fetal heart weights in response to nutrition restriction and overfeeding.…”
Section: Discussioncontrasting
confidence: 44%
“…The fall in fetal insulin in underfed fetuses may have mediated this change due to IGFBP-2 being inversely regulated by this factor (review: Kelley et al 1996). In contrast, fetal plasma IGFBP-3 levels tended to decrease in fetuses from underfed mothers (P<0·2) as previously reported in sheep (Lee et al 1997, Gallaher et al 1998. Earlier studies have reported reduced plasma IGFBP-3 and IGF-I levels and IGF-I mRNA expression in the muscle, lung and kidney of fetal sheep when placental growth was restricted (Kind et al 1995).…”
Section: Discussionmentioning
confidence: 52%
“…Reductions in ovine fetal plasma glucose, insulin and IGF-I have been reported earlier following periods of maternal dietary restriction (Bauer et al 1995, Gallaher et al 1998. Glucose provides the fetus with 30% of its daily carbon and energy requirements in the fed state (Fowden 2001), whilst fetal insulin promotes tissue accretion and cell proliferation in bone and soft tissue (Fowden 1989(Fowden , 1995.…”
Section: Discussionmentioning
confidence: 97%
“…Nissen et al (2005) also observed no alteration in foetal serum IGF-1 concentrations or glucose concentrations, an indicator of nutrient supply, with different feed allocations in gestation. In contrast, studies in guinea pigs (Dwyer and Stickland, 1992) and sheep (Gallaher et al, 1998) reported decreased foetal IGF-1 concentrations when maternal feed intake during pregnancy was restricted. IGF-1 can induce nitric oxide production in endothelial cells.…”
Section: Discussionmentioning
confidence: 95%